EPIDEMIOLOGICAL DETERMINANTS OF DENGUE HEMORRHAGIC FEVER (DHF): A LITERATURE REVIEW - Rost, Esther Kendek; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus through the bite of the Aedes mosquito, especially Aedes aegypti . Dengue fever is the fastest growing mosquito-borne disease in the world. Tropical and sub-tropical climate countries are at high risk of transmission of the virus. The aim of this paper is to provide an overview of the epidemiological determinants of dengue hemorrhagic fever (DHF) in Indonesia. The method used in this research is a literature review using a comprehensive strategy by collecting articles through searches in several databases, namely Google Scholar, using the following keywords: